The “New” Performance Funding in Higher Education - Mary P. McKeown-Moak (Educational Considerations, 2013)
Over the past several years, public higher education, both in the U.S. and internationally, has increasingly been required to explain, defend, and validate its performance and value to a wide variety of constituents, including governors, legislators, students, parents, employers, and taxpayers.
Keywords: institutions; accountability; funding; efficiency; enrollments; paradigm; performance; research; higher education